Advancing electrochemical jet methods through manipulation of the angle of address - Mitchell-Smith, Jonathon; Speidel, Alistair; Clare, A.T. (Elsevier, 2018)
Electrochemical jet processing techniques have traditionally been considered to be limited to planar interactions with the electrolyte jet being maintained normal to the workpiece surface. In this study, the viability and resultant effects of articulating the nozzle relative to the work were investigated for the first time. Two machining conventions were defined, normal, where the jet is maintained perpendicular to the traverse direction, and push/pull, where the nozzle is rotated with respect to the direction of travel. It was found, with the normal convention that a range of differing resultant profile surface geometries could be created; unique to this process. This was demonstrated by the changing resultant side wall slopes found through the rotation of the head with up to 80% difference between the slopes of the cut walls. The adjacent wall to the nozzle slope decreasing as the jet angle approaches 90° whilst the opposite side wall slope increases. Predictable ratios of the differing slopes of the striation side walls were then able to be defined. The push/pull convention demonstrated that deeper, sharper cuts are possible due to the highly localising current density effect of nozzle inclination achieving a 35% increase in depth without requiring additional energy. Also, that resultant surface finish could be greatly improved, reducing the profile roughness (Ra) from 0.2 μm in the pull mode to 0.04 μm in the push mode achieving a mirror-like finish. The mechanics of these phenomena are investigated and defined. The influence of nozzle jet speed variation combined with inclining the jet was also studied. This was found to have no noticeable influence on the resultant profile when the nozzle is inclined. In contrast, when the nozzle is normal to the surface, jet velocity is seen to have a direct influence due to polarisation effects relating to the poor clearance of machining debris and the formation of oxides. It is shown that through variation of the angle of jet address an extra level of flexibility and performance is possible within electrochemical jet processes.